Meta‐Research on Oncology Trials: A Toolkit for Researchers with Limited Resources. (16th May 2018) - Riechelmann, Rachel P.; Péron, Julien; Seruga, Bostjan; Saad, Everardo D.
Abstract: : "Meta‐research" is a discipline that investigates research practices. Meta‐research on clinical trials is an attempt to summarize descriptive and methodological features of published or ongoing clinical trials, including aspects of their implementation, design, analysis, reporting, and interpretation. In this type of investigation, the unit of analysis is a primary source of information about a clinical trial (e.g., published reports, study protocols, or abstracts), with meta‐research being a second layer of information that summarizes what is known from various primary sources. After the formulation of the primary research question, the methodology of meta‐research resembles that of other research projects, with predefined eligibility criteria, exposure variables, primary and secondary outcomes of interest, and an analysis plan. This type of study usually provides a high‐level picture of the literature on a specific topic, always accompanied by a critical evaluation of the methodology and/or the quality of reporting of the studies included. Because relatively few resources are consumed to produce meta‐research, these studies offer a great opportunity for clinical scientists working in settings with limited resources. In this article, we present the principles of designing and conducting meta‐research and use our experience to suggest recommendations on how to perform and how to report this type of potentially very creative study. Implications for Practice: The term meta‐research pertains to a type of study in which the unit of analysis is, in most cases, the publication of a clinical trial. This type of study usually provides a high‐level picture of the literature on a specific topic, always accompanied by a critical evaluation of the methodology, design, and/or the quality of reporting of the studies included. Because relatively few resources are consumed to produce meta‐research, these studies offer a great opportunity for clinical scientists who work in low‐income countries. This article presents the principles of designing and conducting meta‐research and proposes practical recommendations on how to perform and report this type of potentially very creative study. Abstract : This article explores the topic of meta‐research and provides methodological guidance to those with interest in the field. Problems and practical solutions are discussed, and guidance on how to report meta‐research studies is offered.